2021
DOI: 10.3354/meps13626
|View full text |Cite
|
Sign up to set email alerts
|

Desperate times call for desperate measures: non-food ingestion by starving seabirds

Abstract: Food deprivation may decrease selectivity in food; however, (1) whether animals can cross a selectivity threshold whereby they ingest non-nutritive items ('non-food') in lieu of food (engaging in pica/lithophagia), (2) their behaviour, or (3) the implications of these behaviours are not documented. By examining carcasses of seabirds that ingested pumice of known provenance prior to death, we provide insights into whether wild animals starve because they have eaten non-food, or whether they eat non-food because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The same feeding behaviour is also seen in the fin whale ( Balaenoptera physalus ) and basking shark ( Cetorhinus maximus ), two marine species studied with regard to environmental pollution by microplastic debris 43 . When marine wildlife such as turtles, seabirds, and whales mistake floating plastic waste for prey, most die of starvation, as their stomachs become filled with plastic debris 44 , 45 . We are concerned that a similar situation may occur with filter-feeding fishes mistakenly consuming pumice stones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same feeding behaviour is also seen in the fin whale ( Balaenoptera physalus ) and basking shark ( Cetorhinus maximus ), two marine species studied with regard to environmental pollution by microplastic debris 43 . When marine wildlife such as turtles, seabirds, and whales mistake floating plastic waste for prey, most die of starvation, as their stomachs become filled with plastic debris 44 , 45 . We are concerned that a similar situation may occur with filter-feeding fishes mistakenly consuming pumice stones.…”
Section: Resultsmentioning
confidence: 99%
“…On the island of Okinawa, pumice covered a wide area of the coast, which may alter the behavior patterns of various organisms associated with the area. Although the Okinawa rail is not a seabird a recent study reported that migratory birds ingest pumice stones when they were starving 45 . Changes in the behaviors of migratory birds in areas where pumice rafts occupy fishing areas or have been washed ashore may require more attention.…”
Section: Resultsmentioning
confidence: 99%
“…As migration southbound is swift and direct (Carey et al, 2014), ingested plastic/associated contaminants likely reflect exposure in the North Pacific. Most (88%) short-tailed shearwaters retain ingested plastic in their gut when traveling south (Roman et al, 2021b). Therefore, the significant detection of multiple additives in the preen gland samples from this species is not unexpected.…”
Section: Case-examination Of Plastic Ingestion By Seabirdsmentioning
confidence: 87%
“…Over the past several decades, there has been growing awareness of the ubiquity of plastic pollution in the natural environment and the multitude of impacts it has on living organisms and ecosystems. Plastic pollution is a chemical stressor: it leaches toxic substances over time, which may induce hepatic stress, affect reproductive success, and lead to increased rates of mortality in living organisms. , Plastic can also cause physical damage through entanglement or through a false sense of satiation , when it is ingested. Plastic can alter the cycling of carbon and nitrogen as it breaks down. The multidimensional nature of plastic pollution makes it a wicked problem that transcends geographic boundaries, warranting global cooperation.…”
Section: Introductionmentioning
confidence: 99%
“…5−8 Plastic pollution is a chemical stressor: it leaches toxic substances over time, 9−11 which may induce hepatic stress, 12 affect reproductive success, 13 and lead to increased rates of mortality in living organisms. 13,14 Plastic can also cause physical damage through entanglement 15−17 or through a false sense of satiation 18,19 when it is ingested. Plastic can alter the cycling of carbon and nitrogen as it breaks down.…”
Section: ■ Introductionmentioning
confidence: 99%